Identification of novel interferon responsive protein partners of human leukocyte antigen A (HLA-A) using cross-linking mass spectrometry (CLMS) approach - Singh, Ashita; Padariya, Monikaben; Faktor, Jakub; Kote, Sachin; Mikac, Sara; Dziadosz, Alicja; Lam, Tak W; Brydon, Jack; Wear, Martin A; Ball, Kathryn L; Hupp, Ted; Sznarkowska, Alicja; et al. (Scientific reports, 2022)
The interferon signalling system elicits a robust cytokine response against a wide range of environmental pathogenic and internal pathological signals, leading to induction of a subset of interferon-induced proteins. We applied DSS (disuccinimidyl suberate) mediated cross-linking mass spectrometry (CLMS) to capture novel protein-protein interactions within the realm of interferon induced proteins. In addition to the expected interferon-induced proteins, we identified novel inter- and intra-molecular cross-linked adducts for the canonical interferon induced proteins, such as MX1, USP18, OAS3, and STAT1. We focused on orthogonal validation of a cohort of novel interferon-induced protein networks formed by the HLA-A protein (H2BFS-HLA-A-HMGA1) using co-immunoprecipitation assay, and further investigated them by molecular dynamics simulation. Conformational dynamics of the simulated protein complexes revealed several interaction sites that mirrored the interactions identified in the CLMS findings. Together, we showcase a proof-of-principle CLMS study to identify novel interferon-induced signaling complexes and anticipate broader use of CLMS to identify novel protein interaction dynamics within the tumour microenvironment.
Keywords: HLA Antigens; interferony; reagencia zkříženě vázaná; proteiny; HLA-A antigeny; Cross-Linking Reagents; Ubiquitin Thiolesterase; hmotnostní spektrometrie; lidé; Interferons; HLA-A Antigens; Mass Spectrometry; Proteins; thiolesterasa ubikvitinu; Humans; HLA antigeny